The Role of Human Resources Training and Development in Increasing Sales at Motorcycle Dealers in Medan Tembung - Raihan, Muhammad; Syahreza, Dina Sarah; Fahyed, Fadhil Al; Julian, Teuku Rendy; Ananda, Tanya (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This research aims to analyze the impact of training and human resource development (HR) on the increase in sales at motorcycle dealers in Medan. In the increasingly competitive automotive industry, motorcycle dealers must improve their service quality and sales strategy. This research uses a quantitative approach with a sample of 80 employees from various motorcycle dealers in Medan. The results of the analysis show that HR training and development has a significant positive impact on sales performance. Effective training improves the technical and non-technical skills of employees, while human resource development contributes to motivation and job satisfaction. These findings emphasize the importance of investing in training and development to achieve competitive advantage in the automotive market.